Les fureurs d'un physicien quantique. Quelques remarques sur le style de Michel Houellebecq - Beránková, Eva (Verbum – Analecta Neolatina, 2006)
Although Michel Houellebecq makes a provocative claim that in literature he places content above form, there is a growing debate about his style in the academic world. By analyzing three of the author's novels we find that all of them consist roughly of three stylistic levels. Whereas the basic level is designed as deliberately neutral ("shallow") writing based on sciences or non-fiction, Houellebecq often does not hesitate to rise to purely lyrical heights or, conversely, revert to the most vulgar language. It is using slang or argot French that enables the writer to create his own original style which can perhaps be only compared to Celine. In the same way as his predecessor, Houellebecq overwhelms readers with an outpour of swearwords; he drowns them in a sea of malicious remarks. Nevertheless, these verbal provocations are not self-serving. However paradoxical it may sound, Michel Houellebecq is above all a very original moralist. His cynical "in fact", a kind of variation of La Rochefoucauld's "is... only", aims at destroying illusions, removing masks and liberating European society from the dictatorship of political correctness. Only in this way is it possible, he claims, to escape what he calls today's "slow suicide of the West".